Dynamic analysis on single-rotor multi-input helicopter main gearbox related with structural parameters - Zhang, Wei; An, Luling (Sage, 2019)
Combined with the finite element method and the lumped mass method, the integral node dynamic model of a single-rotor multi-input helicopter main gearbox is established. The influence of shaft parameters on dynamic characteristics is analyzed, and each torsional shaft is regarded as a finite element node to derive the system dynamic equation. In addition, the dynamic model of the meshing pair element is established by lumped mass method, and these elements not only include internal excitations such as time-varying meshing stiffness and transmission error, but also carry the external load. The differential equations of the system are solved by the Fourier series method. The dynamic responses of the converging element and the planetary gear train are obtained. The load-sharing coefficients of these elements are calculated by the influence of the shaft structural parameters. A parameter optimization method is proposed to improve the system load characteristics, which provides a theoretical support for the design of helicopter main transmission system
Keywords: parameter optimization; load-sharing analysis; shaft flexibility; LMM-FEM mixed modeling; Single-rotor multi-input helicopter